Peningkatan Mutu Kemasan Produk Roti SIP Menggunakan Metode Quality Function Deployment (QFD) untuk Meningkatkan Kepuasan Konsumen (Studi Kasus pada Teaching Factory Bakery Politeknik Negeri Jember): Improving the Packaging Quality of SIP Bread Products Using the Quality Function Deployment (QFD) Method to Enhance Consumer Satisfaction (A Case Study at the Teaching Factory Bakery, Politeknik Negeri Jember) - Eka Ardhi Pratama, Fredy; Bachri, Syaiful; Wahyu Winadi Atmajaya, Aditya; Kusuma Wardani, Dyah; Andini, Paramita (Politeknik Negeri Jember, 2026)
This study aimed to analyze consumer requirements for SIP bread packaging and determine technical improvement priorities using the Quality Function Deployment (QFD) method. The research was conducted at the Teaching Factory Bakery of Politeknik Negeri Jember using a quantitative descriptive approach. Data were collected through observation, interviews, and questionnaires distributed to 50 consumers, then analyzed using the House of Quality (HOQ) matrix. The results showed that the most important packaging attributes were the ability to protect bread quality, packaging safety and cleanliness, and the completeness of label information. Competitive assessment indicated that SIP bread packaging was still relatively comparable to competing products. Based on absolute weights, the main improvement priorities included packaging safety and cleanliness, completeness of label information, packaging design attractiveness, and packaging material strength. On the technical side, the highest priorities were packaging material type and visual design..